Study of Pathological Changes Resulting from Eimeria necatrix in Broiler Breeders (Journal of Hama University, 2019)
Coccidiosis in chickens is one of the most common and distributed diseases, which can lead to serious economic losses due to mortality and low feed conversion rate because of the destruction of the intestine.E.necatrix is one of the most dangerous species of Eimeria affecting chickens especially broiler breeders, which often infected between 9 and 14 weeks of age and the target location of infection is the central part of the intestine that changes occurs in it.Post-mortem examination to 140 samples of intestinal of broiler breeders was performed to determine the intensity of pathological changes resulting from effect Eimeria Necatrix that showed the existence of the intestine is dilated to twice of its normal size ( ballooning ), and the lumen may be filled with blood ,tissue debris and fluid laden with clusters of large mature schizonts.                                                                                                                                       Histopathology of midgut from affected birds reveals a submucosa and lamina propria crowded with large clusters of schizonts.often,large areas of the mucosa are sloughed off, and lesion may extend through the muscle layers to near the serosal membranesScores of infection were divided into four degrees according to the severity of the infection, and (4) was the most severe.It was noted that the highest incidence of infection was (3) with 39.28%, followed by the most severe infection (4) with 32.14%, followed by (2) with 17.85%, and finally (1) with 10.7% which was the lowest according to severity of changes and observations.